Lateral medullary infarction with similar features of Brown Sequard syndrome caused by vertebrobasilar dysplasia and Klippel–Feil syndrome: A case report. Issue 45 (November 2017) - Han, Jingzhe; Cao, Duanhua; Ma, Guomei; Wang, Tingting; Ji, Ye; Kang, Zhilei
Abstract: Rationale: Patients with Klippel–Feil syndrome (KFS) are always anomaly associated with vertebrobasilar dysplasia. That may present commonly as infarction of brainstem, medulla, and cerebellum. In this article, we reported a rare case of lateral medullary infarction (LMI) with similar features of Brown Sequard syndrome caused by vertebrobasilar dysplasia and KFS, and the 2 rare conditions that are causally related. The case is being reported because of its unusual and rare presentation. Patient concerns: A 38-year-old female presented with acute unsteadiness, along with a tendency to lean to the left side while walking or sitting, and paresthesia in the right lower limb and trunk, at 2 days before admission. She had no history of hypertension and diabetes, but had a 20 years history of neck pain and dizziness, which was related to head movement. Diagnoses: Brown Sequard syndrome and a lesion of the left thoracic spinal cord were suspected initially. KFS was confirmed by the cervical magnetic resonance imaging (MRI) and computed tomographic angiography (CTA) results. Transcranial Doppler (TCD) results confirmed that there was a causal link between LMI and KFS. Interventions: The patient rejected the operation of stabilization of the cervical spine with fusion at appropriate levels. Outcomes: No recurrence of stroke, but neck pain and dizziness remained after 6 months of discharge. Lessons: For such patients, the conventional treatment of cerebral infarction might be ineffective, but stabilization of the cervical spine with fusion at appropriate levels can successfully prevent further episodes of syncope and stroke.